Facile one-pot multicomponent synthesis and molecular docking studies of steroidal oxazole/thiazole derivatives with effective antimicrobial, antibiofilm and hemolytic properties - Ansari, Anam; Ali, Abad; Asif, Mohd; Rauf, Mohd Ahmar; Owais, Mohammad; Shamsuzzaman (Steroids, 2018)
A series of steroidal oxazole and thiazole derivatives have been synthesized employing thiosemicarbazide/semicarbazide hydrochloride and ethyl 2-chloroacetoacetate with a simple and facile one-pot multicomponent reaction pathway. The antimicrobial activity of newly synthesized compounds were evaluated against four bacterial strains namely Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes) in addition to pathogenic fungi (Candida albicans and Cryptococcus neofonnans). Bioactivity assay manifested that most of the compounds exhibited good antimicrobial activity. To provide additional insight into antimicrobial activity, the compounds were also tested for their antibiofilm activity against S. aureus biofilm. Moreover, molecular docking study shows binding of compounds with amino acid residues of DNA gyrase and glucosamine-6-phosphate synthase (promising antimicrobial target) through hydrogen bonding interactions. Hemolytic activity have been also investigated to ascertain the effect of compounds over RBC lysis and results indicate good prospects for biocompatibility. The expedient synthesis of steroidal heterocycles, effective antibacterial and antifungal behavior against various clinically relevant human pathogens, promising biocompatibility offer opportunities for further modification and potential applications as therapeutic agents.

Microwave-assisted MgO NP catalyzed one-pot multicomponent synthesis of polysubstituted steroidal pyridines - Ansari, Anam; Ali, Abad; Asif, Mohd; Shamsuzzaman (New Journal of Chemistry, 2018)
The present study reports a highly efficient and green synthetic route for the synthesis of steroidal pyridines. The synthetic methodology involves a microwave-assisted one-pot multicomponent reaction using MgO NPs as a heterogeneous, mild and reusable catalyst. The synthesized MgO NPs were characterized by FTIR, TGA/DTA and XRD analyses. The remarkable features of this protocol include simple operational procedure, shorter reaction profiles, mild reaction conditions, minimal chemical waste and economic viability. The recyclability of the catalyst and high yield of products make the proposed method a sustainable alternative.

Discovery of a novel oxadiazine derivative of glucocorticoids endowed with DNA binding activities and molecular docking studies - Sultanat; Ali, Abad; Asif, Mohd; Rizvi, Asim; Farhan, Mohd; Zaman, Shamsuz (Journal of Taibah University for Science, 2019)
A series of new glucocorticoid oxadiazines (4-6) were synthesized by reacting glucocorticoids (1-3) with thiosemicarbazide and its derivatives. The structural assignment of products is confirmed on the basis of IR, H-1 NMR, C-13 NMR, MS and analytical data. The synthesized compounds (4-6) obeyed the Lipinski's "Rule of Five" analysis based on a computational prediction of molecular and pharmacokinetic properties. The interaction studies of compounds (4-6) with DNA were carried out by employing single-cell gel electrophoresis (comet assay), UV-vis and fluorescence spectroscopy. Compounds (4-6) were found capable of cellular DNA degradation breakage in isolated normal human lymphocytes. Viscometric and steady-state measurements further correlated with the comet assay studies. Hence, it could be suggested that the glucocorticoid compounds bearing a core oxadiazine scaffold would be a potent biological agent. Molecular docking studies further characterize the interaction of the synthesized compounds with DNA.

Steroidal thiazolidinone derivatives: design, synthesis and their molecular interaction with human serum albumin - Ansari, Anam; Ali, Abad; Asif, Mohd; Shamsuzzaman (Steroids, 2019)
A series of steroidal thiazolidinone derivatives have been synthesized through one-pot multicomponent reaction involving steroidal ketone, thiosemicarbazide/methyl-thiosemicarbazide and DMAD in presence of AlCl3 as a Lewis acid catalyst. Among all the synthesized steroidal thiazolidinone derivatives, compound 7-9 (ST 7-9) were investigated for their in vitro molecular interaction with human serum albumin. Intrinsic fluorescence spectroscopy, constant wavelength synchronous fluorescence spectroscopy, circular dichroism and UV-visible absorption techniques have been exploited to characterize the binding phenomena in phosphate buffer solution at pH 7.4. The experimental results indicated that ST 7-9 bind to HSA and the intrinsic fluorescence of HSA was quenched through static quenching mechanism. The binding parameters were calculated and the binding constants obtained were 1.44 x 10(5) M-1 for ST 7, 0.84 x 10(5) M-1 for ST 8 and 1.06 x 10(5) M-1 for ST 9. Circular dichroism analysis confirms that the presence of ST 7-9, altered the secondary structure of HSA due to partial unfolding of the polypeptide chain. Furthermore, hemolytic activity assay demonstrated that the synthesized steroidal thiazolidinone derivatives have good compatibility towards human red blood cells. Finally, molecular docking studies revealed that the steroidal thiazolidinones can bind in the hydrophobic cavity of HSA, by hydrophobic and hydrogen bonding interaction. These results provided valuable information about the binding mechanism of ST 7-9 with HSA and play a pivotal role in the development of steroidal heterocycle inspired compounds.
Keywords: heterocycles; Human serum albumin; steroids; Thiazolidinone